Juvenile Delinquent Pupils' Perceptions On The Teaching Of Islamic Education: A Preliminary Study - Asmawati Suhid; Fathiyah Mohd Fakhruddin; Abd. Muhsin Ahmad; Lukman Abdul Mutalib (Human Resource Management Academic Research Society, 2024)
Indexed by ERA